Detection of HIV-1 drug resistance in women following administration of a single dose of nevirapine: Comparison of plasma RNA to cellular DNA by consensus sequencing and by oligonucleotide ligation assay - Thor A. Wagner (2018)
A single dose of nevirapine (sdNVP) to prevent mother-to-child transmission of HIV-1 increases the risk of failure of subsequent NVP-containing antiretroviral therapy (ART), especially when initiated within 6 months of sdNVP administration, emphasizing the importance of understanding the decay of nevirapine-resistant mutants. Nevirapine-resistant HIV-1 genotypes (with the mutations K103N, Y181C, and/or G190A) from 21 women were evaluated 10 days and 6 weeks after sdNVP administration and at the initiation of ART. Resistance was assayed by consensus sequencing and by a more sensitive assay (oligonucleotide ligation assay [OLA]) using plasma-derived HIV-1 RNA and cell-associated HIV-1 DNA. OLA detected nevirapine resistance in more specimens than consensus sequencing did (63% versus 33%, P < 0.01). When resistance was detected only by OLA (n = 45), the median mutant concentration was 18%, compared to 61% when detected by both sequencing and OLA (n = 51) (P < 0.0001). The proportion of women whose nevirapine resistance was detected by OLA 10 days after sdNVP administration was higher when we tested their HIV-1 RNA (95%) than when we tested their HIV-1 DNA (88%), whereas at 6 weeks after sdNVP therapy, the proportion was greater with DNA (85%) than with RNA (67%) and remained higher with DNA (33%) than with RNA (11%) at the initiation of antiretroviral treatment (median, 45 weeks after sdNVP therapy). Fourteen women started NVP-ART more than 6 months after sdNVP therapy; resistance was detected by OLA in 14% of the women but only in their DNA. HIV-1 resistance to NVP following sdNVP therapy persists longer in cellular DNA than in plasma RNA, as determined by a sensitive assay using sufficient copies of virus, suggesting that DNA may be superior to RNA for detecting resistance at the initiation of ART. Copyright © 2010, American Society for Microbiology. All Rights Reserved.